Prevalence of Early Childhood Caries in Children of West Godavari District, Andhra Pradesh, South India: An Epidemiological Study - Koya, Srikanth (Int J Clin Pediatr Dent, 2016)
AIM: To determine the prevalence of early childhood caries (ECC) and its risk factors in children of West Godavari district, Andhra Pradesh. STUDY DESIGN: A sample of 1,897 children between 24 and 71 months of age based on stratified cluster random sampling were clinically examined for dental caries using mouth mirror under day light. The parents/caregivers of each child were interviewed with a structured questionnaire. Data was analyzed using independent sample Student’s t-test and chi-square test. RESULTS: Out of the total 1,897 children, 796 were affected with ECC showing an overall prevalence of 41.9%, with boys showing a higher prevalence rate of 44.8% compared to girls (39.9%). Statistically significant correlations were found between ECC and consumption of sugary snacks (p < 0.0001) and mouth rinsing habit (p < 0.001). CONCLUSION: A higher prevalence of ECC was observed and most of the teeth were not restored. HOW TO CITE THIS ARTICLE: Koya S, Ravichandra KS, Arunkumar VA, Sahana S, Pushpalatha HM. Prevalence of Early Childhood Caries in Children of West Godavari District, Andhra Pradesh, South India: An Epidemiological Study. Int J Clin Pediatr Dent 2016;9(3):251-255.